Large, Stable, Contemporary Interspecies Recombination Events in Circulating Human Herpes Simplex Viruses. (23rd April 2019) - Casto, Amanda M; Roychoudhury, Pavitra; Xie, Hong; Selke, Stacy; Perchetti, Garrett A; Wofford, Haley; Huang, Meei-Li; Verjans, Georges M G M; Gottlieb, Geoffrey S; Wald, Anna; Jerome, Keith R; Koelle, David M; et al.
Abstract: Background: The ubiquitous human pathogens, herpes simplex virus (HSV)-1 and HSV-2, are distinct viral species that diverged approximately 6 million years ago. At least 4 small, ancient HSV-1 × HSV-2 interspecies recombination events have affected the HSV-2 genome, with recombinants and nonrecombinants at each locus circulating today. However, it is unknown whether interspecies recombination can affect other loci and whether new recombinants continue to be generated. Methods: Using 255 newly sequenced and 230 existing HSV genome sequences, we comprehensively assessed interspecies recombination in HSV. Results: Our findings show that the sizes and locations of interspecies recombination events in HSV-2 are significantly more variable than previously appreciated and that they can impact species-specific T-cell recognition of HSV. Conclusions: We describe 2 large (>5 kb) recombination events, one of which arose in its current host, demonstrating that interspecies recombination continues to occur today. These results raise concerns about the use of live-attenuated HSV-2 vaccines in high HSV-1 prevalence areas. Abstract : A comprehensive survey of approximately 500 HSV genomes reveals HSV-1 × HSV-2 recombination events up to 7 kilobases in length at loci across the HSV-2 genome and demonstrates that novel interspecies recombinants continue to be generated.